THE MEDIATING ROLE OF SELF ESTEEM IN PERSONALITY AND MENTAL HEALTH PROBLEMS IN UNIVERSITY STUDENTS WITH TRAUMATIC EXPERIENCES - Samia Rani; Sadia Saleem; Sayyeda Taskeen Zahra (Journal of Postgraduate Medical Institute, 2023)
Objective: The current study explores the mediating role of self-esteem in the relationship of extraversion and mental health problems in traumatized university students. Methodology: For this purpose, from the list of 265 total 215 potential participants were selected for further steps, who marked the “happened to me” on Life Event Checklist 29. A sample of 215 university students (men = 31%; women = 69%) with the ages of 18 to 26 (M= 20.78; SD= 2.46). Self-Esteem Scale for University Students, Big Five Personality Inventory, and Depression Anxiety Stress Scale were used to assess the self-esteem, extraversion, and mental health problems of the participants. Results: Results of correlation analysis indicated the positive association of extraversion and self-confidence (r =.136, p < .05*), anxious self-esteem and mental health problems (r = 541, p <.001***). Furthermore, results also suggested the negative association of extraversion and anxious self-esteem (r = 257, p < .001***), extraversion and mental health problems (r = 218, p < 05*), self-confidence and mental health problems (r = 138, p < .05*). However, low self-esteem, resilience, and sociability were not related with extraversion and mental health problems. Subsequently, mediation analysis indicated the significant mediating role of anxious self-esteem and self-confidence in the association of extraversion and mental health problems. Conclusion: These findings indicated that boosting the self-esteem level of can ensure the psycho-social well-being of traumatized university students.